Maimonides on the origin of the world - Seeskin, Kenneth (Cambridge University Press, 2005)
Although Maimonides' discussion of creation is one of his greatest contributions - he himself claims that belief in creation is second in importance only to belief in God - there is still considerable debate on what that contribution was. Kenneth Seeskin takes a close look at the problems Maimonides faced and the sources from which he drew. He argues that Maimonides meant exactly what he said: the world was created by a free act of God so that the existence of everything other than God is contingent. In religious terms, existence is a gift. In order to reach this conclusion, Seeskin examines Maimonides' view of God, miracles, the limits of human knowledge, and the claims of astronomy to be a science. Clearly written and closely argued, Maimonides on the Origin of the World takes up questions of perennial interest.